Comparative Analysis of Different CPU Scheduling Algorithms with Respect to Average Waiting Time and Average Turnaround Time - Samanta, Biswarup; Biswas, Arinjay (Mathematics and Computer Science: Research Updates Vol. 5, 2025)
CPU scheduling is one of the fundamental concepts of an Operating System. Most CPU scheduling algorithms concentrate on maximising CPU utilisation and throughput and minimising turnaround time, waiting time, response time and number of context switches for a set of requests. Some of the popular CPU scheduling algorithms are First-Come-First-Served (FCFS), Shortest Job First (SJF), Priority Based (PB) and Round Robin (RR). It has been found that CPU scheduling algorithms serve as the basis of multiprogramming. This paper presents the relationship between existing CPU scheduling algorithms with respect to their average waiting time and average turnaround time through different cases. There are five cases where each of which has four parts, and each part represents different existing CPU scheduling algorithms, i.e. FCFS, SJF, RR, and PB. Each part assumes that there are four different processes with different or the same priority and arrival time depending upon the particular case, as designed in the Section 4 of this paper. The goal of this paper is to find out the relationship with respect to average waiting time and average turnaround time, when different cases are implemented on the existing CPU scheduling algorithms and find the fastest algorithm amongst the existing CPU scheduling algorithms taken in this article. Case Formulation- In case 1, the CPU bursts taken are 4, 3, 5 and 2 for all the respective 4 processes. In case 2, the CPU burst taken is an addition of 1 from the CPU burst of case 1 of each process. In case 3, the CPU burst taken is the subtraction of 2 from the CPU burst of case 2 of each process. In case 4, the CPU burst taken is an addition of 3 from the CPU burst of case 3 of each process. In case 5, the CPU burst taken is the addition of 1 from the CPU burst of case 4 of each process.